Role of L-Arginine/Nitric Oxide Pathway in the Antinociceptive Activities of Morphine and Mepyramine in Mice - Abacioğlu, Nurettin; Özmen, Rüya; Çakici, İclal; Tunçtan, Bahar; Kanzik, İlker (Arzneimittelforschung, 2001)
The p-benzoquinone (PBQ) -induced abdominal constriction test was used to assess the involvement of L-arginine/nitric oxide (NO) pathway in the antinociceptive activity of the subcutaneously administered H1-receptor antagonist, mepyramine (CAS 59-33-6), and an opioid receptor agonist, morphine (CAS 57-27-2), in mice. Mepyramine (ED50: 5.6 mg/kg) and morphine (ED50: 0.13 mg/kg) produced antinociceptive effects. The NO precursor L-arginine (CAS 1119-34-2) (50 mg/kg) also produced antinociception similar to mepyramine, but significantly less than morphine. The NO synthase (NOS) inhibitor L-NG-monomethylarginine (L-NMMA) (CAS 53308-83-1) (50 mg/ kg) did not significantly change p-benzoquinone-induced abdominal constrictions. L-arginine significantly increased the antinociceptive effects of morphine and mepyramine. The antinociceptive activity of morphine, but not that of mepyramine, was completely abolished when combined with L-NMMA. L-NMMA also significantly decreased the antinociception induced by morphine or mepyramine in combination with L-arginine. The present results suggest that morphine and mepyramine could produce peripheral antinociception by the involvement of L-arginine/NO cascade or other related pathways of nociceptive processes induced by NO.
Keywords: L-Arginine/nitric oxide, mouse, role in antinociception; CAS 57-27-2; CAS 59-33-6; Mepyramine, antinociception; Morphine, antinociception